Oral Ibrexafungerp Outcomes in Subjects With Refractory Vulvovaginal Candidiasis From an Open-Label Study (FURI) [A122]. (May 2022) - Goje, Oluwatosin; King, Thomas; Angulo, David; Azie, Nkechi
Abstract : INTRODUCTION: Ibrexafungerp, a novel one-day oral triterpenoid antifungal, was recently approved for the treatment of vulvovaginal candidiasis (VVC). Ibrexafungerp is a fungicidal with broad activity against Candida species, including fluconazole-resistant strains. We present data from an open-label Phase 3 study (FURI), which enrolled patients with refractory VVC utilizing a 3-day dose ibrexafungerp regimen. METHODS: FURI VVC subjects were included if they had proven or probable severe VVC, with evidence of treatment failure, intolerance, or toxicity to a currently approved standard-of-care antifungal treatment. Subjects with VVC received ibrexafungerp monotherapy given as oral doses of 375 mg twice daily every three days for a total of three dosing days (Day 1, Day 4, and Day 7). Global Response or Clinical Improvement, defined as complete or partial resolution of signs and symptoms with total vaginal signs and symptoms composite score<1, without need for additional antifungal, was measured at Day 17. RESULTS: There were 14 VVC patients enrolled in FURI from 2019 to 2021. All patients had previously failed other therapies, including fluconazole, and were referred to an infectious disease specialist at a tertiary-care setting. Global response measured at Day 17 indicated that 12 patients (85.7%) had clinical improvement, one patient had partial improvement and one patient was deemed indeterminate. Adverse events for ibrexafungerp were predominantly gastrointestinal, with mild-to-moderate diarrhea, nausea, and abdominal pain. CONCLUSION: These results demonstrate the therapeutic potential of a 3-day dose of oral ibrexafungerp for the treatment of patients with VVC who have failed other treatments.